Chironomus blaylocki sp. n. and C. bifurcatus sp. n., North American species near the base of the decorus-group (Diptera: Chironomidae) - Wuelker, Wolfgang; Martin, Jon; Kiknadze, Iya I.; Sublette, James E.; Michiels, Susanne (Zootaxa, 2009)
Two species of the cytologically defined Chironomus decorus-group, C. bifurcatus sp. n. and C. blaylocki sp. n., are described on the basis of their salivary gland polytene chromosomes and larval morphology, with the associated male and pupa of C. bifurcatus and the putative male of C. blaylocki included as paratypes. The banding patterns of the salivary gland chromosomes indicate that these species are near the base of the cytologically defined decorus-group. The cytology and adults of these new species are compared with those of a number of other undescribed North American decorus-group species to demonstrate that they are distinct species.